FAKTOR PENYEBAB BERALIHNYA KONSUMEN OJEK PANGKALAN MENJADI OJEK ONLINE - Arum Wahyuni Purbohastuti (FEB Universitas Sultan Ageng Tirtayasa, 2018)
This study aims to determine the factors that influence consumer decisions in using transportation on line. Where the object of the research is the D3 Marketing Students of Sultan Ageng Tirtayasa University in 2015, 2016 and 2017.The method used in this study is a qualitative method that is descriptive research and tends to use analysis. The sample taken was 15 people.Based on the research that has been done, the choice of online transportation selection is influenced by factors including price, practical and efficient, service quality and security. Keywords: Trademark, Brand Transfer, Online Transportation, and Conventional Transportation, price, practical and efficient, service quality and security.